Abusive supervision, psychosomatic symptoms, and deviance: Can job autonomy make a difference? - Velez, M. J.; Neves, P. (Journal of Occupational Health Psychology, 2016)
Recently, interest in abusive supervision has grown (Tepper, 2000). However, little is still known about organizational factors that can reduce its adverse effects on employee behavior. Based on the Job Demands-Resources Model (Demerouti, Bakker, Nachreiner, & Schaufeli, 2001), we predict that job autonomy acts as a buffer of the positive relationship between abusive supervision, psychosomatic symptoms and deviance. Therefore, when job autonomy is low, a higher level of abusive supervision should be accompanied by increased psychosomatic symptoms and thus lead to higher production deviance. When job autonomy is high, abusive supervision should fail to produce increased psychosomatic symptoms and thus should not lead to higher production deviance. Our model was explored among a sample of 170 supervisor-subordinate dyads from 4 organizations. The results of the moderated mediation analysis supported our hypotheses. That is, abusive supervision was significantly related to production deviance via psychosomatic symptoms when job autonomy was low, but not when job autonomy was high. These findings suggest that job autonomy buffers the impact of abusive supervision perceptions on psychosomatic symptoms, with consequences for production deviance.